Hubungan antara Sikap Kerja dengan Musculoskeletal Disorders (MSDS) Pada Dokter Gigi di Rumah Sakit Gigi dan Mulut Saraswati - Dewa Made Candra Pramarta; Ni Wayan Rusni; Made Dharmesti Wijaya (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2024)
[The Relationship between Work Attitudes and Musculoskeletal Disorders (MSDS) in Dentists at Saraswati Dental and Oral Hospital] Musculoskeletal disorders (MSDs) are work-related problems that are highly highlighted globally. Work posture is the position of the body during work activities when interacting with work facilities in a work station. Musculoskeletal complaints are complaints regarding the skeletal muscle pains, from the lightest of complaints to the most severe. The aim of this study is to determine the correlation between work posture with MSDs on dentists in Saraswati Dental and Oral Hospital. This analytical research with cross sectional design was conducted on March-April 2022. A total of 60 respondents were selected for this study using simple random sampling method. The data was measured using Nordic Body Map (NBM) for MSDs and Rapid Entire Body Assessment (REBA) questionnaires for Work posture. The data were analyzed using SPSS 25. The results of the univariate analysis was showed as follow : the the risk of working posture and category of MSDs were 50 % (moderate) and 43.3 % (heavy), respectively while the bivariate was analyzed using the Spearman Rank test was showed the score of p < (0,05) with the score of r = 0,83. The conclusion could be drawn that there was an significantce correlation between work posture with MSDs. It was recommended that the working posture of dentist should be ergonomics approach.